ANALISIS PELAKSANAAN MODEL PEMBELAJARAN EXAMPLES NON EXAMPLES DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN SOSIOLOGI KELAS XI IPS 3 DI MAN 1 PONTIANAK - Sulavi, Rafilah Putri; Okianna, Okianna; Ramadhan, Iwan (Universitas Tanjungpura, 2024)
This study explores enhancing student learning outcomes by applying the examples non examples learning model in sociology education. Employing a qualitative methodology, this investigation adopts a descriptive approach to research. Primary data sources include a sociology instructor from MAN 1 Pontianak's class XI IPS 3 and four students from the same class. The focus is on assessing the effectiveness of planning, execution, and the outcomes associated with this educational strategy in sociology. The study's findings reveal that the Learning Implementation Plan (RPP) is the primary framework for organizing learning activities, focusing on social mobility and conflict. Educators adhere to this plan during the sociology lessons through a structured approach consisting of introductory, leading, and concluding phases, utilizing the examples non examples model. This methodology aligns with the predefined RPP, ensuring a comprehensive educational process. The educational approach aligns with the phases prescribed by the examples non examples model of instruction. Conducted across two sessions, this method has demonstrated an enhancement in student learning outcomes.